Evaluasi Clinical Pathway Seksio Sesarea: Keefektifan Penggunaan Antibiotika Injeksi Cefotaxime 2 Gram dalam 24 Jam untuk Mencegah Terjadinya Infeksi Luka Operasi - Rathi Manjari Fauziah; Rukmono Siswishanto; Shofwal Widad (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2016)
Background: The usage of prophylactic antibiotics in Dr. Sardjito Hospital, Yogyakarta, is still diverse. Previously, prophylactic antibiotics that were given would be in a form of multidose and or multidrug regimen. Recently, a clinical pathway for c-section had been set up to uniform the antibiotics given. Cefotaime 2g, given intravenously, in 24 hours is the antibiotic of choice. Unfortunately, there was no data about the effetiveness of cefotaime that can be used as a basis of clinical pathway. Objective: Comparing the incidence of surgical site infection (SSI) between cefotaime 2g,/24 hours (clinical pathway or CP) with previous regimen of prophylactic antibiotics (non-clinical pathway or nonCP) and also identify the risk factors.Method: This is a retrospective cohort study with 129 subjects, divided into two groups. The CP group consists of 63 subjects, while non-CP group consists of 66 subjects. The surgical site infection was observed in the day 3 and day 10 aer C-section. Multivariat analysis was used to determine the risk factors of SSI.Result and Discussion: SSI incidence in the CP group at day 3 was higher compared to non-CP group, but it was not statistically significant (OR 4,73 95% CI 0,52 43,04), eukocytosis (>17000/mcl) was the independent risk factor for SSI (OR 7,54 95% CI 1,25 45,39).Conclusion: SSI incidence between two groups was not statistically significant but was clinically significant. The presence of leukocytosis is becoming the risk factor for SSI.Keywords: prophylactic antibiotic, c-section, cesarean section, surgical site infectio